Visual perception and robotic manipulation : 3D object recognition, tracking and hand-eye coordination - Taylor, Geoffrey (Geoffrey Richard); Kleeman, Lindsay (Berlin : Springer, 2006)
Accompanying CD-ROM contains ...'video clips, VRML data, C++ code with data sets and lecture slides.'--P. [4] of cover.
Book is accompanied by one CD entitled' Visual perception and robotic manipulation : 3D object recognition, tracking and hand-eye coordination' bearing the same call number and is available at Bahagian Koleksi Media
Includes bibliographical references (p. [207]-216) and index.
System requirements for disc: Windows 2000 or Windows XP; CD-ROM drive
Keywords: Robot vision; Computer vision